Case-report: Massive infection by Cysticercus longicollis in a captive Lemur catta from Italy - Cuccato, Matteo; Rubiola, Selene; Rossi, Luca; Piga, Sara; Scaglione, Frine Eleonora (Frontiers in Veterinary Science, 2023)
An adult male ring-tailed lemur (Lemur catta) from a biopark of northern Italy was submitted to necropsy. A multi-organ parasitic infection was macroscopically evident. Abundant sero-hemorrhagic fluid with larval parasites was present in all cavities. The microscopic evaluation of parasites and the molecular characterization revealed the presence of Cysticercus longicollis (the larval stage of Taenia crassiceps). Histology of liver, lungs, intestine and urinary bladder revealed several larval parasites surrounded by a severe lymphocytic infiltrate, fibrous tissue and hemorrhages. This is the first report of a ring-tailed lemur with an infection of C. longicollis in Italy. The source of infection is still not known however, the discovery of this parasite in a captive lemur poses more attention on the control of parasitic diseases implementing monitoring tests and biosecurity measures.